2017
DOI: 10.1111/pim.12397
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immune genes in skin of channel catfish immunized with live theronts of Ichthyophthirius multifiliis

Abstract: The objective of this study was to evaluate differential expression of innate and adaptive immune genes, including immunoglobulin, immune cell receptor, cytokine, inflammatory protein, toll-like receptors (TLR) and recombination-activating gene (RAG) in skin from channel catfish, Ictalurus punctatus after immunization with live theronts of Ichthyophthirius multifiliis (Ich) by intraperitoneal injection. The immunized catfish showed significantly higher survival rate (95%) than those of mock-immunized control f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
0
6
0
2
Order By: Relevance
“…The gene for iNOS has been partially sequenced in both trout (Laing et al, 1999) and goldfish (Laing et al, 1996) and it is shown to be inducible after challenge in vivo with bacterial pathogen or in vitro with LPS. iNOS was also upregulated in channel catfish, Ictalurus punctatus after immunization with live theronts of Ichthyophthirius multifiliis (Moreira et al, 2017). However, NO production is not selectively targeted to microorganisms and has the potential to be toxic to host tissues in high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The gene for iNOS has been partially sequenced in both trout (Laing et al, 1999) and goldfish (Laing et al, 1996) and it is shown to be inducible after challenge in vivo with bacterial pathogen or in vitro with LPS. iNOS was also upregulated in channel catfish, Ictalurus punctatus after immunization with live theronts of Ichthyophthirius multifiliis (Moreira et al, 2017). However, NO production is not selectively targeted to microorganisms and has the potential to be toxic to host tissues in high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In a brief experiment, TLRs were up-regulated (TLR8a1, TLR8a2, TLR8b1, TLR19, TLR20a, TLR22a1, and TLR22a2) and down-regulated (TLR3, TLR8b2, TLR9, TLR18, and TLR21) in the kidney of rainbow trout during natural PKD infection [34]. Moreover, intraperitoneal injection of live theront life stages of I. multifiliis modulated the expression of TLRs in channel catfish (Ictalurus punctatus) [35].…”
Section: Introductionmentioning
confidence: 98%
“…The parasite targets both wild and cultured fish but the huge economic impact of the protozoan is associated with mortality, morbidity, prevention and treatment in aquaculture facilities (Dickerson & Findly, 2017). The infected fish may mount a protective immune response (Bauer, 1953; Burkart, Clark, & Dickerson, 1990; Buschkiel, 1910; Dickerson & Clark, 1998; Goven, Dawe, & Gratzek, 1980; Hines & Spira, 1974; Moreira, Shoemaker, Zhang, & Xu, 2016; Sigh & Buchmann, 2001; Wang, Yu, Zhang, & Xu, 2019), but the experimental vaccines investigated so far (Burkart et al., 1990; He et al., 1997; Jørgensen et al, 2017; Ling, Sin, & Lam, 1993; Martins, Xu, Shoemaker, & Klesius, 2011; Wang, Clark, Noe, & Dickerson, 2002; Xu, Zhang, Shoemaker, & Beck, 2019) have not yet resulted in a marketable protective formulation. A number of chemotherapeutants have been successfully applied in the laboratory (Al‐Jubury et al., 2018; Picon‐Camacho, Marcos‐Lopez, & Shinn, 2012), but at farm level frequent usage of formalin, peracetic acid, sodium percarbonate and hydrogen peroxide remains the preferred control strategy (Heinecke & Buchmann, 2009; Meinelt et al., 2009; Rach, Gaikowski, & Ramsay, 2000).…”
Section: Introductionmentioning
confidence: 99%